Sentencing and public confidence: Results from a national Australian survey on public opinions towards sentencing - Mackenzie, G.; Spiranovic, C.; Warner, K.; Stobbs, N.; Gelb, K.; Roberts, Lynne; Broadhurst, R.; Bouhours, T. (Sage, 2012)
This paper examines the critical issue of public confidence in sentencing, and presents findings from Phase I of an Australia-wide sentencing and public confidence project. Phase I comprised a nationally representative telephone survey of 6005 participants. The majority of respondents expressed high levels of punitiveness and were dissatisfied with sentences imposed by the courts. Despite this, many were strongly supportive of the use of alternatives to imprisonment for a range of offences. These nuanced views raise questions regarding the efficacy of gauging public opinion using opinion poll style questions; indeed the expected outcome from this first phase of the four phase sentencing and public confidence project. The following phases of this project, reported on elsewhere, examined the effects of various interventions on the robustness and nature of these views initially expressed in a standard ‘top of the head’ opinion poll.